Ferrar large igneous province: petrology - Elliot, David H.; Fleming, Thomas H. (Geological Society, London, Memoirs, 2021)
The Lower Jurassic Ferrar Large Igneous Province consists predominantly of intrusive rocks, which crop out over a distance of 3500 km. In comparison, extrusive rocks are more restricted geographically. Geochemically, the province is divided into the Mount Fazio Chemical Type, forming more than 99% of the exposed province, and the Scarab Peak Chemical Type, which in the Ross Sea sector is restricted to the uppermost lava. The former exhibits a range of compositions (SiO2 = 52–59%; MgO = 9.2–2.6%; Zr = 60–175 ppm; Sri = 0.7081– 0.7138; εNd = −6.0 to −3.8), whereas the latter has a restricted composition (SiO2 = c. 58%; MgO = c. 2.3%; Zr = c. 230 ppm; Sri = 0.7090–0.7097; εNd = −4.4 to −4.1). Both chemical types are characterized by enriched initial isotope compositions of neodymium and strontium, low abundances of high field strength elements, and crust-like trace element patterns. The most basic rocks, olivine-bearing dolerites, indicate that these geochemical characteristics were inherited from a mantle source modified by subduction processes, possibly the incorporation of sediment. In one model, magmas were derived from a linear source having multiple sites of generation each of which evolved to yield, in sum, the province-wide coherent geochemistry. The preferred interpretation is that the remarkably coherent geochemistry and short duration of emplacement demonstrate derivation from a single source inferred to have been located in the proto-Weddell Sea region. The spatial variation in geochemical characteristics of the lavas suggests distinct magma batches erupted at the surface, whereas no clear geographical pattern is evident for intrusive rocks. © 2021. The Author(s).
7 citations (Crossref) [2023-10-31]
Keywords: dept.esc; peer-reviewed